Effect of Mg on Inclusion and High Cycle Fatigue Behavior in Titanium Microalloyed Beam Steel - Zhijun Gao; Guangfei Pan; Shuize Wang; Yu Song; Honghui Wu; Xinping Mao (Metals, 2023)
In this paper, the fatigue behavior of titanium microalloyed beam steels were studied by high cycle fatigue test and fatigue crack growth rate test. The effect of Mg addition on the fatigue behavior in titanium microalloyed beam steel was systematically analyzed. According to the experimental results, the addition of magnesium can effectively modify the inclusions by reducing the size of Al2O3 and TiN and promoting the formation of finer complex inclusions with a MgO·Al2O3 core in titanium microalloyed high-strength beam steel. The number of inclusions in the experimental steels had far less of an impact on the fatigue characteristic than inclusion size. With the heterogeneous nucleation effect of MgO·Al2O3, the inclusions are refined after the Mg addition. The tensile strength of Beam-2 steel decreased by approximately 54 MPa, while its fatigue strength increased by about 33 MPa, showing favorable fatigue resistance. These findings are essential for optimize the fatigue properties of titanium microalloy steel and promoting the development of automobile beam steel with excellent fatigue properties.